A. f(x) = x2 - 11x - 12
B.f(x) = x2 - 4x -12
C. f(x) = x2+x-12
D. f(x) = x2-x-12
Match each quadratic function given in factored form
with its equivalent standard form listed on the left.
f(x) = (x + 2)(x-6)
f(x) = (x - 4)(x+3)
f(x) = (x – 12)(x + 1)
f(x) = (x – 3)(x +4)

Respuesta :

Answer:

[tex]x^2 -11x-12=(x-12)(x+1)\\x^2 -4x - 12 = (x-6)(x-+2)\\x^2+x-12 = (x-3)(+4)\\x^2-x-12=(x-4)(x+3)[/tex]

Step-by-step explanation:

The sum of the two roots gives you the x term of the quadratic.

Answer:

x^2 -11x-12=(x-12)(x+1)\\x^2 -4x - 12 = (x-6)(x-+2)\\x^2+x-12 = (x-3)(+4)\\x^2-x-12=(x-4)(x+3)

Step-by-step explanation: